COVID-19 Vaccination and Uveitis: Epidemiology, Clinical Features and Visual Prognosis. (4th July 2022) - Ferrand, Nawfel; Accorinti, Massimo; Agarwal, Mamta; Spartalis, Christoph; Manni, Priscilla; Stuebiger, Nicole; Zierhut, Manfred
ABSTRACT: Purpose: To study the epidemiological and clinical features of uveitis post-COVID-19 vaccination. Patients and Methods: Retrospective chart review of patients presenting with uveitis after COVID-19 vaccination in tertiary uveitis services. Results: In total, 25 patients, 76% females, mean age 43.2 years, were included. Uveitis occurred after Pfizer, Moderna, Astra-Zeneca and Covaxin vaccination. Anterior uveitis was the most frequent type of uveitis (56%). History of uveitis was found in 19 cases (76%), among whom 90.9% of the tested patients developed anti-Sars-CoV-2 spike antibodies after vaccination. In a mean follow-up of 5 months, one-line decrease in visual acuity was found in 12% of patients. During post-vaccine uveitis, 15.8% of cases needed an increase in their systemic therapy. According to Naranjo score, new-onset uveitis had a higher probability of being associated with vaccination (p < .01). Conclusion: COVID-19 vaccination can cause uveitis but has no significant impact on the visual prognosis after resolution.